You Must Stay at Home! The Impact of Commands on Behaviors During COVID-19. Issue 1 (January 2022) - Krpan, Dario; Dolan, Paul
"You must stay at home!" This is how the UK Prime Minister announced lockdown in March 2020. Many countries implemented similarly assertive messages. Research, however, suggests that authoritative language can backfire by inciting psychological reactance (i.e., feelings of anger arising from threats to one's autonomy). In a series of three studies, we therefore tested whether commanding versus control and noncommanding messages influence several cognitive and affective indicators of reactance, intentions to comply with COVID-19 recommendations, and the compliance behavior itself. Although people found commanding messages threatening and felt angry and negative toward them, these messages impacted only intentions, but there was no evidence of behavioral reactance. Overall, our research constitutes the most comprehensive examination of cognitive–affective and behavioral indicators of reactance regarding commands to date and offers new insights into both reactance theory and COVID-19 communication.